Systematic Review and Meta-analysis of Alarm versus Desmopressin Therapy for Pediatric Monosymptomatic Enuresis. Issue 1 (December 2018) - Peng, Carol; Yang, Stephen; Austin, Paul; Chang, Shang-Jen
Abstract This study is to compare the efficacy of enuresis alarm and desmopressin therapy in managing pediatric monosymptomatic enuresis. We performed systematic literature searches on different databases from inception until April 2017 without language restriction. All randomized control trials comparing an enuresis alarm and desmopressin in managing children with monosymptomatic enuresis were included. A total of 15 studies with 1502 participants (aged 5 to 16 years) were included for pooled analysis. Overall, an enuresis alarm outperformed desmopressin in achieving at least a partial response (>50% reduction in wet nights) in per-protocol analysis (OR: 1.53, 95% CI 1.05 to 2.23) but not in intention-to-treat analysis (OR: 0.97, 95% CI 0.73 to 1.30) as the alarm was hampered by a high dropout rate (OR: 2.20, 95% CI 3.41 to 4.29). However, alarm therapy yielded a better sustained response (OR: 2.89, 95% CI 1.38 to 6.04) and lower relapse rate (OR: 0.25, 95% CI 0.12 to 0.50). In the intention to treat analysis, the results revealed that alarm and desmopressin therapy are comparable in efficacy with regards to achieving >50% reduction in baseline wet nights in enuretic children. However, enuresis alarms offer a superior treatment response and a lower relapse rate in well-motivated children.